Dihydrotestosterone enhances growth and infectivity of Leishmania Mexicana. (18th January 2018) - Sánchez‐García, L.; Wilkins‐Rodriguez, A.; Salaiza‐Suazo, N.; Morales‐Montor, J.; Becker, I.
Summary: A strong sex‐associated susceptibility towards Leishmania has been reported in males, yet little is known on the effect of hormones in Leishmania physiopathogenicity. Due to the enhanced susceptibility of males to Leishmania   mexicana infections, we were interested in analysing the effect exerted by the main androgen produced in males (DHT) on L. mexicana promastigotes. Thus, the aim of this study was to assess the regulation exerted by dihydrotestosterone (DHT) on L. mexicana replication, infectivity, survival and development of tissue lesions. Experiments included growth curves of L. mexicana promastigotes incubated with different doses of DHT, their infection rate, intracellular survival and lesion development in BALB/c mice. Our data show that DHT significantly enhances parasite replication, infection rate and survival in bone marrow‐derived macrophages (BMMФ). Promastigotes in the presence of DHT produced significantly larger lesions in BALB/c earlobes. These results suggest that DHT probably plays a critical role during L. mexicana infections, and the higher susceptibility of males possibly relates to benefits gained by the parasite from host‐derived hormones. Our data shed new light on the physiopathology of Leishmania infections and are the first attempt to understand the direct interaction between Leishmania and androgens, particularly DHT. Understanding this trans‐regulation process employed by parasites to exploit host molecules sheds new light on L. mexicana physiopathogenesis and opens a possible field for studies on drug development.